One perfect summer ebook A novel. - Novak, Brenda (2020)
"A great book to finish off your summer reading."—Debbie Macomber, #1 New York Times bestselling author Some families we're born into Some we find for ourselves When Serenity Alston swabbed her cheek for a genetic test, she joked about uncovering some dark ancestral scandal. The last thing she expected was to discover two half sisters she didn't know existed. Suddenly, everything about her loving family is drawn into question. And meeting these newfound sisters might be the only way to get answers. The women decide to dig into the mystery together at Serenity's family cabin in Lake Tahoe. With Reagan navigating romantic politics at work and Lorelei staring down the collapse of her marriage, all three women are converging at a crossroads in their lives. Before the summer is over, they'll have to confront the past and determine how to move forward when everything they previously thought to be true was a lie. But any future is easier to face with family by your side. "This heartwarming story of sisters who bond as adults is sure to please...those who enjoy books by Susan Mallery and Debbie Macomber."—Library Journal Don't miss New York Times bestselling author Brenda Novak's latest novel, The Seaside Library! Other charming reads from Brenda Novak: Summer on the Island The Bookstore on the Beach